The Uraśa State and its Capital: Archaeology and History-based Investigations: https://doi.org/10.55966/assaj.2025.4.1.089 - Shakirullah; Muhammad Zahoor (`, 2025)
Inspite of the several vicissitudes of time in the last two millennia which brought hordes of alien peoples and cultures into Hazāra, its original Uraśā or Araśa still survives in the Damtauṛ or Dhamtauṛ valley, Abbotabad. The level plain of Dhamtaur valley is locally known as Rush or Arash. The name variants recorded by the ancient writers were: Arash, Arsa, Uraśa and Uragā. It can be seen that the absence of a complete uniformity in the spelling is most evident. It is not unlikely therefore that the original spelling was Aruśa which, in the course of time, changed into Uraśa. If so, it would give us the key to elucidate the enigmatic Dhamtauṛ (correctly Dharmtauṛ = Religious Enclosure) and determine the name of a god (deity) to whom the worship was dedicated. Monier William’s Sanskrit Dictionary records that Aruśa was a designation of all important and favourite gods of the Vedic Aryans (Monier-Williams 1970). It is quite natural that the lands adjacent to the ‘Enclosure’ (Pl.Ia, b) with the lapse of time also came to be known after the name of the god, Aruśa (Indra), corrupted into Arash or Rash. Xuan Zang does not name the capital but mentions the existence of a stupa and monastery 4 or 5 li (1km) to the south of it (Beal 1884). A recent survey conducted by the writers confirms the truthfulness of this statement. Much dilapidated remains of a Buddhist establishment at the site of Mochikot (Pl.Ia, b)were seen at about the same distance from Māngal, the probable capital of Rash. Keywords: Uraśa, Araśā, Arsa, Rash, Aruśa, Pāṇini, Xuan Zang, Ptolemy, Mahābhārata, Rājatarańgiṇi, Dhamtauṛ, Māngal, Mochikot Uraśa/Arsa, (or whatever its uncorrupted pristine form), as the name of a territory which is well preserved in ancient accounts such as Pāṇini (c.4th century BCE), Ptolemy (2nd century CE), Xuan Zang (7th century CE), Kalhaṇa (12th century CE) and Mahābhārata (4th century BCE to 4th century CE).